2017
DOI: 10.1111/modl.12392
|View full text |Cite
|
Sign up to set email alerts
|

Word Reading in L1 and L2 Learners of Chinese: Similarities and Differences in the Functioning of Component Processes

Abstract: This study examined the similarities and differences in the functioning of component processes underlying first language (L1) and second language (L2) word reading in Chinese. Fourth‐grade Chinese children in Singapore were divided into L1 and L2 reader groups based on whether they used Mandarin or English as their home language. Both groups were administered a battery of tasks that assessed their orthographic processing skill (OP), phonological awareness (PA), morphological awareness (MA), oral vocabulary kno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 79 publications
(154 reference statements)
0
15
2
Order By: Relevance
“…Notably, our findings differed from the morphological insensitivity identified by D. Zhang (2017) and Zhou and McBride (2013) in child English-Chinese bilingual learners. D. Zhang (2017) found that orthographic and phonological skills were significant predictors of Chinese word reading in the English-speaking child learners of Chinese in Singapore and observed a positive effect of MA on word reading in native Chinese children only, not in English-speaking children.…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…Notably, our findings differed from the morphological insensitivity identified by D. Zhang (2017) and Zhou and McBride (2013) in child English-Chinese bilingual learners. D. Zhang (2017) found that orthographic and phonological skills were significant predictors of Chinese word reading in the English-speaking child learners of Chinese in Singapore and observed a positive effect of MA on word reading in native Chinese children only, not in English-speaking children.…”
Section: Discussioncontrasting
confidence: 99%
“…As to the language-specific facet of Chinese MA, three frequently cited measures are homophone awareness, lexical compounding awareness, and semantic radical awareness (as cited in Wang, Cheng, & Chen, 2006). Homophone awareness refers to the ability to differentiate different morphemes in homophones (see D. Zhang, 2017). For example, in both 商业 and 商品,, the first character 商 has the same sound /shāng/ and the same meaning "related to business", whereas in 商量, 商, /shāng/ means "to discuss".…”
Section: Defining and Measuring Ma In Chinesementioning
confidence: 99%
See 3 more Smart Citations